Managerial Versus Production Wages: Offshoring, Country Size and Endowments - Sebastian Benz; Wilhelm K. Kohler (Verein für Socialpolitik, 2010)
We look at managerial and production wages in countries that differ in size and relative endowments. Production labor is assumed to be a variable input composed of tradable tasks, while managerial labor is a fixed, non-tradable input. Task performance is subject to increasing returns to scale on the country level, as in Grossman & Rossi-Hansberg (2009). We first analyze country size and relative endowment effects on wages, ruling out task trade altogether, followed by numerical simulations highlighting the degree of freeness of task trade as an important further determinant of relative wages, both within and across countries.
Keywords: F12; F16; F23; 330; Offshoring; Skill Premium; Scale Effect